Guests at our own tables: Privilege, paradox, and Southern hospitality. (August 2019) - Ritter-Conn, Beth
As is true of any region experiencing significant migration, the identity of the US South, and with it the identity of Nashville, Tennessee, is shifting. Both the city and the region have the opportunity to embrace this shift, wrestling collectively with the question of what kind of city we want to be . The lesson of the New Testament, particularly of Luke's Gospel, is that transformation of individuals and communities often happens around the table. With new tables around which to gather and new community members to get to know, the possibility of expanding the meaning of "Southern hospitality" continually presents itself anew. Such an expansion requires both embracing the paradox of guest and host, and remembering our past rightly to learn from the mistakes and the triumphs of the ones who came before us.